Working Capital Management, Firm Performance, Financial Constraints in Building Construction Sub-Sector During COVID-19 Pandemic - Rahmawati, Mega Tri; Irawan, Tony; Santoso, Moch. Hadi (Indonesian Journal of Multidisciplinary Science, 2023)
The building construction sub-sector companies have the lowest profitability with company value continuing to decline but the most efficient working capital turnover compared to other sub-sectors in the infrastructure sector during 2018-2020. Two construction company ownership, namely BUMN and private companies, facing different financial constraints in financing working capital. The purpose of this research is to find out the differences in working capital management, firm performance, and financial constraints before and during the Covid-19 pandemic in the private companies and BUMN. Furthermore, the research attempts to see the influence of working capital management with and without the interaction of financial constraints on firm performance. This study used 12 samples of building construction sub-sector companies listed on the IDX in the 2018q-2021q using paired tests and panel data regression. The results showed that both private and BUMN experienced significant changes in the working capital management component, decreased firm performance, and increased financial constraints during the pandemic. The working capital management has a negative and significant impact on firm performance. The results of interaction between working capital management and financial constraints show that companies experience financial constraints have lower investment levels on working capital due to the expensive cost of funding. The interaction variable strengthens the effect of the cash conversion cycle on firm performance.